Behavior of Photovoltaic System during Solar Eclipse in Prague. (2nd February 2016) - Libra, Martin; Kouřím, Pavel; Poulek, Vladislav
Abstract : PV power plants have been recently installed in very large scale. So the effects of the solar eclipse are of big importance especially for grid connected photovoltaic (PV) systems. There was a partial solar eclipse in Prague on 20th March 2015. We have evaluated the data from our facility in order to monitor the impact of this natural phenomenon on the behavior of PV system, and these results are presented in the paper. The behavior of PV system corresponds with the theoretical assumption. The power decrease of the PV array corresponds with the relative size of the solar eclipse. I -V characteristics of the PV panel correspond to the theoretical model presented in our previous work.